"The Grand Elixir:" Swift, Anatomy, Immortality, and the Self-Reflexive Text - Bates, Tamara K. (My University, 1995)
When Swift, In "Verses on the Death of Dr. Swift, D.S.P.D.," imagines the fate of his works, his lament sounds suspiciously like that of the Modern Author of A Tale of a Tub. Swift's anxiety regarding his literary longevity extends throughout his corpus, from the Tale and Gulliver's Travels to the "Verses," indicating that this was indeed a real concern for him. Swift's attempt to avoid that fate involves his representation of the carnival-grotesque body, embodying Bakhtin's "material bodily principle" (Rabelais and His World, p.18), which insists on the ambivalence of the representation -- the degredation of the body enables its regeneration. By including the body, its functions, and its decay in his literature, Swift effectively creates a great deal of controversy regarding such a representation. This controvesy is what keeps the works in the critical arena.
The critical arena was important to Swift. While he may have been anxious about the new criticism being propounded by the Moderns, Swift also recognized that without that arena, his works would be "sunk in the Abyss of Things" (Tale, p.32). For Swift, this criticism involves dialogue, and with it a form of dialogism, which, in Bakhtin's sense, allows the existence, not only of multiple worldviews, but of multiple interpretations of texts. This multiplicity causes controversy, which generates conversation, and through that conversation, Swift hopes to attain literary immortality.
Keywords: English Language and Literature; English Language and Literature